Constructing identity in and around organizations - Schultz, Majken (Oxford : Oxford University Press, 2012)
This volume focuses on the notion of identity, in particular how individual and organisational identities evolve and come to be constructed through on-going activities and interactions.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Organizational behavior; Group identity